Analysis of the Role of Content Review Through the TikTok Application in Increasing Brand Awareness Among Generation Alpha: A Case Study of SMP Hang Tuah 2 - Patricya Damanik; Salman Munthe (Economic: Journal Economic and Business, 2025)
This study aims to analyze the role of content reviews through the TikTok application in increasing brand awareness among Generation Alpha with a case study of students of Hang Tuah 2 Middle School. Based on the author's findings, 100% of pre-survey respondents stated that TikTok is a very popular platform, and 86% of them often view skincare product review content. However, Generation Alpha has not been able to distinguish objective content from those that are merely marketing strategies. This study uses a quantitative method. This study aims to enable Generation Alpha to be wiser and more critical in assessing the authenticity and objectivity of review content on social media. The study population was 160 students of Hang Tuah 2 Middle School. The number of samples was determined as 115 respondents using a purposive sampling technique with the Slovin formula with a margin of error of 5%. Data were analyzed using simple linear regression using the SPSS 25 application. The results of the t-test showed that content reviews (X) had a positive and significant effect on brand awareness (Y). The coefficient of determination value of 0.612 indicates that 61.2% of the proportion of brand awareness is influenced by content reviews, while the remaining 38.8% is influenced by other variables. Thus, TikTok can be an effective and strategic medium for building brand awareness among young audiences.